PENDAMPINGAN PEMBUATAN ARTIKEL GURU SEKOLAH DASAR DI SDN 2 GANTI KECAMATAN PRAYA TIMUR - Pahru, Syaipul; Pransisca, Made Ayu; Rizal, Samsul; Marzuki, Ahmad Dedi; Hadi, Samsul; Gazali, Munawir; Yuliani, Meri; Habibi, Muhamad Ridwan (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
This PKM activity was carried out at Elementary School Institutions in Ganti Village, East Praya District, namely at Ganti Elementary School as a partner. The design mechanism for implementing PKM activities is carried out by adopting action research steps which consist of 4 (four) stages, namely: planning, action, observation and evaluation, and reflection. Activities or activities from each stage, namely (1) Planning, at this stage initial coordination is carried out between the team proposing the partnership program and the partner school team to identify existing problems, analyze partner needs, and analyze school potential, then arrange training programs, (2) Implementation of Actions, Actions in this activity are in the form of program implementation. The activities carried out in program implementation include; the formation of the Implementation Team, and the implementation of the article writing workshop, (3) Observation and Evaluation, Observations were made of the process of making articles by partner teachers. The instrument used is in the form of field notes, the final stage is (4) Reflection. Reflection is carried out on the activities that have been carried out.